1998
DOI: 10.1123/japa.6.3.285
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship of Lactate to 1-Mile Walk Performance in Women Aged 60 to 70 Years

Abstract: The purpose of this study was to examine the relationship between selected physiological variables and lactate accumulation at the end of a l-mile walk test (MWT) in older women (mean ± SD: 64.6 ± 3.1 years). Seventeen women with a peak (ml · kg-1 · min-1) of 21.1 ± 4.2 volunteered to participate. Physiological data were obtained via a COSMED K2 miniaturized O2 analyzer with telemetric capabilities during a maximal treadmill (TM) test and MWT. Blood samples were obtained from the ear lobe for lactale analysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 0 publications
2
3
0
Order By: Relevance
“…The walking times for RFWT and RFWTCosmed for older women were similar (16.18 ±2.22 min and 16.0 ± 1.93 min, repectively) and comparable to other studies (Fenstermaker et al, 1992;Bazzano et al, 1998). 1-mile walking times in older women (age 69.4±4.2 years) were 16.99 ± 2.17 min and 16.73 ± 2.12 min (Fenstermaker et al, 1992) for walk 2 and 3 in a series of 3.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…The walking times for RFWT and RFWTCosmed for older women were similar (16.18 ±2.22 min and 16.0 ± 1.93 min, repectively) and comparable to other studies (Fenstermaker et al, 1992;Bazzano et al, 1998). 1-mile walking times in older women (age 69.4±4.2 years) were 16.99 ± 2.17 min and 16.73 ± 2.12 min (Fenstermaker et al, 1992) for walk 2 and 3 in a series of 3.…”
Section: Discussionsupporting
confidence: 65%
“…19.01 ± 4.18 min). Bazzano et al (1998) reported walking times of 15.4±1.4 min for older women (64.6±3.1 years). In our study, the log transformed LoA for walking time showed individuals with relatively long walk times to have greater variation when performing the second walk.…”
Section: Discussionmentioning
confidence: 99%
“…Together, the [La] and HR responses indicate that the 6 MWT was performed at sub-maximal effort. Previous authors reported that the blood lactate and the HR max during the 1-Mile walk test have a direct relationship in healthy elderly adults (Bazzano, Cunningham, Cama, & Falconio, 1998). These background and the data of the current study, suggest that the metabolic variable (lactate) and heart rate are good indicators to control the intensity during the field exercise testing at least in apparently healthy elderly people.…”
Section: Discussionsupporting
confidence: 71%
“…Although using indirect calorimetry to estimate VO 2max , is a limitation of this study, Bazzano et al [23] have determined that the 1-mile walk test is a suitable field testing procedure for elderly women, resulting in valid estimates of VO 2max . Despite the increase in cardiovascular fitness, there were few group differences noted for immune parameters after the 10-week period.…”
Section: Discussionmentioning
confidence: 99%
“…This test was completed again after 10 weeks of training. Bazzano et al [23] determined that this is a suitable field testing procedure for elderly women.…”
Section: Cardiac Screening and Testingmentioning
confidence: 99%